The Influence of Land Use Change toward Hydrological Aspect at Upper Site - Hidayat, Firman (International Journal of Psychosocial Rehabilitation, 2020)
The impact of land-use change not only gives some benefit to the community but also can cause problems, namely erosion, sedimentation, flooding, and others. Erosion will cause silting of reservoirs, reducing irrigation channel capacity, and disrupting electrical power generation systems. High erosion and flooding in the rainy season not only have a negative impact on the biophysical aspects of natural resources and the environment but also on the social aspects of the economic impact on the community. Several cases of changes in land use in some watersheds in Indonesia are presented with a discussion of the causal relationship of hydrological aspects, especially regarding the carrying capacity of the watershed and the frequency of flooding. Hydrology and runoff characteristics of a number of primary rivers in Indonesia (Java) are presented by using land that increases timely. Related to that case, the research will be taken. The objective is to analyze the influence of land use change on hydrological aspects. At the Mahat Hulu watershed, located in the Lima Puluh Kota district, in 15 years (1995-2010), deforestation has taken a significant amount. In 1995 Watershed has Forest area approximately 50.9%and in 2010, it decrease into 28% or from 14523 ha (1995) to 7981 ha (2010)but mix garden increased from 17.1% (1995) to 43.8% (2010) or 4889 ha (1995) to 12508 ha (2010). Consequently, such as runoff increased, flooding, and drought during the dry season, high erosion and sedimentation, as well as a decline in productivity and income of farmers. In this case, the special aspect that research focused on was the influence of land use changes on the hydrological aspects, such as the coefficient of annual and seasonal runoff and fluctuations. The method used quantitative and multiple regression tests. The result of the analysis is that deforestation will increase coefficient runoff and fluctuations in discharge. Coefficient runoff increased from 20% in 1999-2002 to 24% in 2007-2010, and fluctuation of discharged (KRS) also increased from 2.4-5.5 (1999-2002) to 5.9-10.7 (2007-2010), indicating DAS is critical. Results of multiple regression tests showed a close correlation between the variables (0.9); the formula is C (%) = 975 - 11.2 htn - 15.3 kbn cpr - 10.9 smk blkr + 0.43 tgln, and R-Sq = 42.4%. The stepwise regression test showed that forest area influences runoff. It can be showed from the equation is CRO = 31.5 - 0.370 htn, , R-Sq = 5.3% It means runoff will increase because the forest area has decreased.